PERSEPSI MAHASISWA ILMU KOMUNIKASI FAKULTAS ILMU SOSIAL STAMBUK 2018 UIN SUMATERA UTARA TERHADAP BUSANA SELEBGRAM ANDROGINI DI INSTAGRAM - Dando, Evan; Ritonga, Muhammad Husni; Jailani, Muhammad (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
This research is entitled "2018 UIN North Sumatra communication science students' perceptions of androgynous celebrity fashion on Instagram". The aim of this research is to find out whether there are students' positive perceptions of androgynous celebrity fashion on Instagram. The method used in this research is a descriptive quantitative method. The population in this study was 330 students from the 2018 UIN North Sumatra communication science program. The technique used in sampling was the Slovin formula with a significance level of 10%. So a sample of 77 respondents was determined. The results of the research on the t test with 15 questions on the perception variable showed that students had a positive perception of androgynous celebrity fashion on Instagram.